2016
DOI: 10.18632/oncotarget.14100
|View full text |Cite
|
Sign up to set email alerts
|

A novel nomogram based on LODDS to predict the prognosis of epithelial ovarian cancer

Abstract: BACKGROUNDTo develop and validate a nomogram based on log of odds between the number of positive lymph node and the number of negative lymph node (LODDS) in predicting the overall survival (OS) and cancer specific survival (CSS) for epithelial ovarian cancer (EOC) patients.MATERIALS AND METHODSA total of 10,692 post-operative EOC patients diagnosed between 2004 and 2013 were obtained from the Surveillance, Epidemiology, and End Results (SEER) database and randomly divided into training (n = 7,021) and validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…[19][20][21][22][23] Little is known about the role of LODDS in ovarian cancer. Xu et al 24 found LODDS as an independent prognostic factor for predicting survival in patients with EOC regardless of the tumor stage. Although LODDS exhibits discriminatory ability in predicting survival, there is no study concerning the diverse role of LODDS in different FIGO stages.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[19][20][21][22][23] Little is known about the role of LODDS in ovarian cancer. Xu et al 24 found LODDS as an independent prognostic factor for predicting survival in patients with EOC regardless of the tumor stage. Although LODDS exhibits discriminatory ability in predicting survival, there is no study concerning the diverse role of LODDS in different FIGO stages.…”
Section: Discussionmentioning
confidence: 99%
“…In FIGO stage I, a large number of resected lymph nodes did not represent a better outcome. The patients with [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] RLNs have the best prognosis. When RLNs numbered more than 30, the survival rate decreased.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations